THE EFFECTIVENESS OF ERROR CORRECTION FEEDBACK IN IMPROVING STUDENTSâ WRITING SKILL ( An Experimental Study at English Department of UIN-Ar-Raniry) - Rosdiana, Rosdiana (Getsempena English Education Journal, 2014)
Writing is the way of expressing ideas or opinions in written words. Teaching how to write effectively is one of the most important life-long skills educators impart to their students. When teaching writing, educators must be sure to select resources and support materials that not only aid them in teaching how to write, but that will also be the most effective in helping their students learn to write. As the last stage of writing process, rivising designed to reexamine and reevaluate the studentsâ error in a piece of writing. In this case, error correction feedback become on of important steps to applied in teaching English Writing in order to improve studentsâ writing proficiency. Therefore, this study attempts to identify the effectiveness of error correction feedback in improving studentsâ writing skill at English Department of UIN Ar-Raniry Banda Aceh. The correction focused on the five aspects of writing; content, organization, grammar, word choice and mechanics. This study employed an experimental design. It is intended to find out any significant difference on the studentsâ writing before and after they are taught by applying error correction feedback. The technique of data analysis is using T-test. Having analyzed the statistical computation, it can be concluded that the difference between the two means is significant. By those facts, Ho is rejected and Ha is accepted. Thus, Error Correction Feedback is effective in improving the studentsâ writing ability.Keywords: Error Correction, Writing Ability.